Efecto traspaso de tasas de interés: análisis econométrico de los efectos de las decisiones de política monetaria en República Dominicana (2012)
The study of the transmission mechanisms of central banks’ interest rate decisions is crucial for the design and implementation of an efficient and effective monetary policy. An estimation of how changes in the monetary policy rate pass on to the long-term rates of the economy is known, in empirical literature, as the interest rate pass-through. This paper develops an econometric strategy, based on cointegration, error correction techniques and recursive regressions, to estimate the magnitude, completeness, rigidity and velocity of convergence of the interest rate pass-through in the Dominican Republic, as well as the existence of possible structural changes in such transmission.